Creation and Implementation of Standardised Craniofacial Views for the Institute of Medical Illustrators National Guidelines. (December 2013) - Rowe, Stephanie
<x xml:space="preserve">Abstract</x> Vetter1 states, "Standardisation is the key word in all discussions of clinical photography". As part of clinical photography standardised guidelines form an integral part of providing a basis to obtaining standardised images. The Institute of Medical Illustrators (IMI) provides sets of standardised guidelines that have been developed in consultation with relevant clinicians, providing theory and standardised images that are to be considered as guides to good clinical photography practice. At the time of the study there were no official standardised IMI guidelines for craniofacial photography, for this reason, the primary objective of this project was to produce a set of standardised craniofacial guidelines that could be utilised by other clinical photographers for guidance on taking craniofacial images. This paper describes the development, evaluation and implementation of the guidelines.